DAMPAK MANAJEMEN KUALITAS TOTAL DAN INTEGRASI RANTAI PASOK TERHADAP KINERJA PERUSAHAAN EKSPEDISI - Lumban Gaol, Juan Oscar Maulana; Wahyuningsih; Sigiro, Semton Vicktor (Institut Shanti Bhuana, Program Studi Kewirausahaan, 2024)
Companies need to pay attention to various aspects to achieve success amidst intense competition. Business developments encourage companies to adapt, with company performance and supply chain integration as key factors in success. Company, which operates in the domestic and international expedition sector, must ensure service quality to remain competitive. This research was conducted to determine the impact of supply chain integration on the performance of the Logistc company. This research is included in the type of